1971
DOI: 10.1111/j.1471-0528.1971.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variation in Menstrual Blood Loss

Abstract: Menstrual blood losses were measured in 348 women aged 17 to 45 years in a Northumbrian mining village. Menstrual loss was found to be related to parity and to the birthweight of previous children. It is possibly associated with height, and may be partly controlled by uterine size and blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(51 citation statements)
references
References 13 publications
2
49
0
Order By: Relevance
“…The median menstrual iron loss in European women is approximately 0.45 mg/day, with 75th, 90th, and 95th percentiles of 0.85, 1.35, and 1.75 mg/day, respectively [20][21][22]. As suggested by Hallberg and Rossander-Hultén [23], the menstrual iron losses may be even higher.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The median menstrual iron loss in European women is approximately 0.45 mg/day, with 75th, 90th, and 95th percentiles of 0.85, 1.35, and 1.75 mg/day, respectively [20][21][22]. As suggested by Hallberg and Rossander-Hultén [23], the menstrual iron losses may be even higher.…”
Section: Discussionmentioning
confidence: 97%
“…The use of oral hormonal contraceptives tends to reduce blood losses [3,21,24,25], whereas IUDs tend to increase the losses [3,21,25,26]. The duration of menstrual bleeding was shortest in pill users and longest in IUD users, while those using other contraceptive methods took an intermediate position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain sufficient stores of iron, it is generally recommended that the daily intake (RDI) of dietary iron is 8 mg/ day for adult men, and 18 mg/day for adult women (Food and Nutrition Board, Institute of Medicine, Washington, DC 2001). The higher RDI for women comes as a result of menstrual blood loss, which is estimated to equate to 1.5-2.1 mg/day of iron loss (Cole et al 1971). The body absorbs approximately 6-12% of the total dietary iron consumed daily (Adamson 1999).…”
Section: Iron Metabolismmentioning
confidence: 99%
“…Cole et al [2] suggested that excess menstruation should be considered to be present when more than 80 ml of blood is lost per cycle. However, the initial complaint of menorrhagia is a subjective one and most often originates from the woman's perceived menstrual loss.…”
Section: Introductionmentioning
confidence: 99%